Некоторые задачи построения описанных эллипсоидов - Лаптин, Ю.П. (Теорія оптимальних рішень, 2006)
Some modifications of circumscribed ellipsoid methods are discussed. There are considered the problems which are important for such modifications – the problem of selecting the most essential cutting planes from a set of ones which were accumulated during previous iterations and the problem of circumscribed ellipsoid construction for intersection of sphere and simplex.